2014
DOI: 10.1038/ng.3166
|View full text |Cite
|
Sign up to set email alerts
|

Mutations in the deubiquitinase gene USP8 cause Cushing's disease

Abstract: Cushing's disease is caused by corticotroph adenomas of the pituitary. To explore the molecular mechanisms of endocrine autonomy in these tumors, we performed exome sequencing of 10 corticotroph adenomas. We found somatic mutations in the USP8 deubiquitinase gene in 4 of 10 adenomas. The mutations clustered in the 14-3-3 protein binding motif and enhanced the proteolytic cleavage and catalytic activity of USP8. Cleavage of USP8 led to increased deubiqutination of the EGF receptor, impairing its downregulation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

38
534
5
7

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 502 publications
(605 citation statements)
references
References 37 publications
38
534
5
7
Order By: Relevance
“…In particular, no somatic mutations have been also detected at the gene GPR101, probably due to the low reported frequency of this mutations (11/248 cases) (33), and, at both the exome sequencing and the targeted sequencing, we did not find any mutations of the PRKACA and USP8 genes. These findings further confirm that both these genetic alterations are not involved in the pathogenesis of GH-secreting adenomas (32,36). Interestingly, several non-recurrent alterations affected other genes involved in the cAMP signaling besides GNAS (see Table 2).…”
Section: Discussionsupporting
confidence: 72%
See 1 more Smart Citation
“…In particular, no somatic mutations have been also detected at the gene GPR101, probably due to the low reported frequency of this mutations (11/248 cases) (33), and, at both the exome sequencing and the targeted sequencing, we did not find any mutations of the PRKACA and USP8 genes. These findings further confirm that both these genetic alterations are not involved in the pathogenesis of GH-secreting adenomas (32,36). Interestingly, several non-recurrent alterations affected other genes involved in the cAMP signaling besides GNAS (see Table 2).…”
Section: Discussionsupporting
confidence: 72%
“…Dominant mutations in the deubiquitinase USP8 gene that promote activation of EGFR signaling have been also found in adrenocorticotropin (ACTH)-secreting pituitary adenomas by exome sequencing (36). Finally, germline mutations of genes such as the aryl hydrocarbon receptor-interacting protein (AIP), the menin (MEN1), and the p27 (CDKN1B) have been reported in genetic syndromes associated with acromegaly (i.e., familialisolated pituitary adenoma and multiple endocrine neoplasia type 1 and 4) and in a low percentage of young acromegalic patients (37).…”
mentioning
confidence: 99%
“…Different mechanisms and factors involved in the initiation and progression of pituitary adenomas have been described, including cell-cycle deregulation, overexpression of growth factors, oncogenes and hormones, defective signaling pathways and an altered intrapituitary microenvironment (Clayton & Farrell 2004, Farrell 2006, Dworakowska & Grossman 2009, Colao et al 2010, Vandeva et al 2010, Melmed 2011, Perez-Castro et al 2012, as well as inherited or somatic mutations in genes such as AIP (Vierimaa et al 2006), GPR101 (Trivellin et al 2014) and USP8 (Reincke et al 2015). The recent characterization of pituitary stem cells (Fauquier et al 2008, Garcia-Lavandeira et al 2009, 2015, Vankelecom & Gremeaux 2010 implies the possibility of defining their mechanisms involved not only in pituitary cell renewal but also in pituitary tumorigenesis.…”
Section: Autocrine Il-6 Mediates Pituitary Tumor Senescencementioning
confidence: 99%
“…The presence of senescent cells in the tumor and the relative abundance of different proteins produced by the senescent cells are important biological factors that could have significant prognostic implications for the fate of the disease. The involvement in the senescent process of several oncogenes and mutations recently described in the pituitary (Vierimaa et al 2006, Trivellin et al 2014, Reincke et al 2015 remains an interesting open question.…”
Section: Future Perspectivesmentioning
confidence: 99%
“…POMC promoter activity by EGF required a -323 to -200 bp element that includes Tpit/Pitx sites [18]. Recently Reincke et al reported that ubiquitin-specific peptidase 8 (USP8) gene mutations were found in a high percentage of corticotroph adenomas [19,20]. The USP8 gene mutations enhanced the proteolytic cleavage and catalytic activity of USP8.…”
Section: Discussionmentioning
confidence: 99%